LAYANAN HOME VISIT PENDIDIKAN ANAK USIA DINI BAGI ANAK KURANG SEJAHTERA - ELIS KOMALASARI (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2015)
Early childhood home visiting program to be one of the important components in the system of early childhood education in several countries. In some states in American, these countries have proved the success of early childhood home visiting services program, it can improving health and development in less prosperous families. Early childhood home visiting program is an alternative service in early childhood education which aims to improve access to services in early childhood intervention and meet the needs of early childhood living in conditions of risk and less prosperous families. Based on research, this service can build social capital and encourage the implementation of policies at the national level aimed at the welfare of children.In the practical implementation, early childhood home visiting program involved professionals in education, developmentalis and social workers to provide services to families who have young children and live below the poverty. The services providing education and parental guidance, the practice of home - based play for children , health and child development information, as well as services involving the surrounding community.This paper will (1) Discuss the success of implementation of early childhood home visit program in some countries, (2) examines how the practices of early childhood home visit program in promoting growth and development early childhood in less prosperous families, (3) analyze the mapping of early childhood home visit program in Indonesia to improve early childhood education participation rates in children and families less prosperous.Kata kunci: home visiting program, early childhood education, children at risk